41.2k views
4 votes
Which expression is equivalent to 3(2x+4y)-y? Show your work

A. 17xy
B. 6x+12
C. 3(6xy)-y
D. 6(x+2y)-y

Which expression is equivalent to 3(2x+4y)-y? Show your work A. 17xy B. 6x+12 C. 3(6xy-example-1
User Antonyt
by
5.0k points

1 Answer

10 votes

Hey there!


3(2x + 4y) - y

= 3(2x + 4y) - 1y

= 3(2x) + 3(4y) - 1y

= 6x + 12y - 1y

= 6x + 11y


LETS TEST OPTION D. FOR YOUR RESULT…


Option D.
6(x + 2y) - y

= 6(1x + 2y) - 1y

= 6(1x) + 6(2y) - 1y

= 6x + 12y - 1y

= 6x + 11y


6x + 11y = 6x + 11y which makes this statement TRUE ☑️


Therefore, your answer is:

Option D. 6(x + 2y) - y


Good luck on your assignment & enjoy your day!


~Amphitrite1040:)

User MSalters
by
5.8k points